Photographic appropriation vs. Baroque painting expressiveness. Postmodern artistic practices in Benetton advertising - Cătălin Soreanu (Anastasis: Research in Medieval Culture and Art, 2021)
In this article we analyze from the perspective of vocabulary and visual language elements the way in which the photographic media provides advertising with one of the most consistent expressive resources. The realism of the image, the endless possibilities in managing the visual composition, the premises of reproductibility and, last but not least, the appetite of an audience eager for technological image, ensured the success of this medium acquisition in the field of advertising expression. The way in which photography is used in advertising mechanisms is, instead, the prerogative of the artistic sphere and it is fully subject to professional standards of design, concept, and realization of the image. In particular, we examine how contemporary advertising becomes the territory where various means of expression contribute in a complementary way to the constitution of the meaning of a work, emphasizing the specific sensitivity of those expressive mediums – namely photography and painting. The case study will approach the activity of Oliviero Toscani and his collaboration with Benetton, materialized in memorable advertising campaigns that have practically rewritten the visual history of contemporary advertising. Using “AIDS – David Kirby” ad from Benetton’s “Shock of Reality” advertising campaign from 1992, we will specifically analyze the creative premises and mechanisms that characterize Toscani’s creation, the reading conditions of his advertising works, as well as the way in which his creative strategies combine the expressiveness of the referential painting memory with the technological precision of press photography, and the appropriation artistic strategies specific to postmodernity.